2017
DOI: 10.3390/cancers9010004
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Clinical Significance of Androgen Receptor in Triple-Negative Breast Cancer

Abstract: Background: Triple-negative breast cancer (TNBC) has a poor prognosis because of frequent recurrence. Androgen receptor (AR) is involved in the pathogenesis of breast cancer, but its role is not clearly defined. The aim of this study was to explore the expression of AR and its relationship with clinicopathologic features in TNBC. Methods: This study investigated 1036 cases of sporadic invasive breast carcinoma. Immunohistochemical assays were performed to determine the expression of AR in 190 TNBC samples. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
46
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 38 publications
(65 reference statements)
11
46
2
2
Order By: Relevance
“…Furthermore, we reported that the rate of pCR to NAC was 24.1% for TNBC AR+ group compared with 60% of QNBC group. These findings matched with voluminous previous reports (Hilborn et al, 2016;Gerratana et al, 2018;Masuda et al, 2013;Asano et al, 2016;Asano et al, 2017, andovanović et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, we reported that the rate of pCR to NAC was 24.1% for TNBC AR+ group compared with 60% of QNBC group. These findings matched with voluminous previous reports (Hilborn et al, 2016;Gerratana et al, 2018;Masuda et al, 2013;Asano et al, 2016;Asano et al, 2017, andovanović et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…The results were comparable; the pCR in TNBC AR+ was less frequent than in QNBC. Similarly, Masuda et al through a retrospective study on 146 patients with TNBC, reported lower pCR in TNBC AR+ compared with QNBC (Asano et al, 2017).…”
Section: Discussionmentioning
confidence: 76%
“…It has been reported that AR is expressed in 60–70% of ER − BC and in approximately 68% of the cases in this research . The AR signalling pathway has a significant role in the proliferation and survival of ER − BCs, and inhibition of AR has a therapeutic value in in‐vitro and in‐vivo models of ER − AR + BC cells .…”
Section: Discussionsupporting
confidence: 50%
“…Several studies have shown that AR expression in luminal tumours (ER+) is associated with lower tumour grade, smaller tumour size, lower proliferative index (Ki67 level) and more importantly, AR expression in ER+ tumours is an independent prognostic factor of a good outcome (Castellano et al 2010, Niemeier et al 2010, Aleskandarany et al 2016, Bozovic-Spasojevic et al 2016). On the other hand, up to 31% of ER-negative (ER−) BCs are reported to be AR+ (Niemeier et al 2010, Park et al 2010, but the prognostic impact of AR expression in this subset of BCs is not clear (Luo et al 2010, Hu et al 2011, Park et al 2011, Pistelli et al 2014, Vera-Badillo et al 2014, Hilborn et al 2016, Jiang et al 2016, Asano et al 2017.…”
Section: Introductionmentioning
confidence: 99%